FORMULATION AND EVALUATION OF RAMIPRIL MOUTH DISSOLVING FILMS - E., Jasvanth; D., Teja; B., Mounika; Nalluri, Buchi N. (International Journal of Applied Pharmaceutics, 2019)
Objective: The present investigation was aimed at preparation and evaluation of mouth dissolving films (MDFs) of Ramipril to enhance patient convenience, compliance and to improve bioavailability. Methods: MDFs with 0.5% w/w Ramipril were prepared by a solvent casting method using a wet film applicator. The effects of film formers, wetting/solubilizing, saliva stimulating agents and film modifiers on the physicomechanical and in vitro Ramipril release from MDFs were evaluated. Results: The MDFs prepared were transparent, smooth and showed no re-crystallization upon storage. MDFs casted with hydroxypropyl methylcellulose (HPMC) E3 as film former and polyethylene glycol (PEG-400) as plasticizer showed superior Ramipril release rates and good physicomechanical properties when compared to MDFs with E5 and E15 as film formers. HPMC E3 MDFs with polyvinyl pyrrolidone K30 (PVP K30) and sodium lauryl sulphate (SLS) gave superior drug release properties than MDFs without PVP K30 and SLS. The HPMC E3 MDFs with citric acid (CA) as saliva stimulating and xylitol as soothing agent gave significantly superior in vitro drug release than the MDFs without CA and xylitol. Release kinetics data reveals diffusion as a drug release mechanism. Conclusion: From the obtained results, it can be concluded that the administration of Ramipril as MDF may provide a quick onset of action with enhanced oral bioavailability and therapeutic efficacy.